Korelasi Rasio Kolesterol Total Terhadap HDL dengan Prediksi Outcome Stroke Iskemik Akut - yuziani yuziani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Stroke is the leading cause of death in Indonesia with the significant increase in prevalence each year. The dominant stroke is ischemic stroke which is often caused by abnormal blood lipid profile which is the increase of total cholesterol to High-Density Lipoprotein (HDL) ratio that is an increase of total cholesterol and decrease of HDL. The risk of ischemic stroke will increase if there is an increase of total cholesterol to HDL ratio because it can stimulate the formation of atherosclerosis. The increase of total cholesterol and the low of HDL level after stroke attack will inhibit the recovery, both of them can influence outcomes and increase mortality in ischemic stroke. This study aim is to determine the correlation between total cholesterol to HDL ratio with outcomes prediction of acute ischemic stroke.This study is an analytic study using cross-sectional study design. Sampling studied are all of the acute ischemic stroke patients at General Hospital of Cut Meutia North Aceh District from May to August 2017 used total sampling that met inclusion and exclusion criteria. Analysis of the correlation between total cholesterol to HDL ratio with outcomes prediction of acute ischemic stroke uses Spearman correlation test with a significant degree (α) of 0,01. The result of this study showed that the mean of total cholesterol to HDL ratio was 3,7 (moderate risk) and outcomes prediction of acute ischemic stroke was good. There is a correlation between total cholesterol to HDL ratio with outcomes prediction of acute ischemic stroke (r=- 0,623;p=0,000). Lower total cholesterol to HDL ratio was correlated with better outcomes of acute ischemic stroke. Total cholesterol to HDL ratio can be used as a predictor of ischemic stroke outcomes.